2013
DOI: 10.1016/j.immuni.2013.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt Signaling Negatively Modulates Regulatory T Cell Function

Abstract: Foxp3 is crucial for both the development and function of regulatory T (Treg) cells; however, the posttranslational mechanisms regulating Foxp3 transcriptional output remain poorly defined. Here, we demonstrate that T cell factor 1 (TCF1) and Foxp3 associates in Treg cells and that active Wnt signaling disrupts Foxp3 transcriptional activity. A global chromatin immunoprecipitation sequencing comparison in Treg cells revealed considerable overlap between Foxp3 and Wnt target genes. The activation of Wnt signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
154
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(166 citation statements)
references
References 48 publications
11
154
0
1
Order By: Relevance
“…Unlike these TNFR family members that support Treg differentiation by lowering the required TCR threshold, TCF7 could act antagonistically to restrict generation, exclude low TCR affinities, and, thereby, help to shape the Treg TCR repertoire toward higher-affinity clones. Interestingly, a recent study demonstrated that Tregs from Tcf7-deficient mice are perfectly functional and, if anything, were even more potent in suppression assays (50).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike these TNFR family members that support Treg differentiation by lowering the required TCR threshold, TCF7 could act antagonistically to restrict generation, exclude low TCR affinities, and, thereby, help to shape the Treg TCR repertoire toward higher-affinity clones. Interestingly, a recent study demonstrated that Tregs from Tcf7-deficient mice are perfectly functional and, if anything, were even more potent in suppression assays (50).…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of CCR8 and CCL4 indicates that TIGIT signaling may promote Treg migration and retention in tumor tissue (28,29). Interestingly, TIGIT signaling decreased expression of TCF7, which has recently been shown to antagonize the FOXP3-driven transcriptional program in Tregs (30). Thus, TIGIT signaling in Tregs may favor Treg stability.…”
Section: 5mentioning
confidence: 99%
“…Although lung epithelial-and fibroblast-specific roles of Wnt signaling relevant to fibrosis have been described (16,17), less is understood about how Wnt signaling affects the immune system of the lung. Recent reports suggest that Wnt/b-catenin signaling may have opposing effects in different immune cell types (18)(19)(20)(21). In a mouse model of inflammatory bowel disease, activation of b-catenin signaling in CD11c 1 CD11b…”
Section: Clinical Relevancementioning
confidence: 99%